Global Capitalism and De-industrialization of the Textile Industry in Nigeria: A Prognostic Analysis - JACOB, James Nda; OWHOR, Nathan Oviri; JACOB, Mercy Monosoko (Socialscientia: Journal of Social Sciences and Humanities, 2022)
The textile sector of the manufacturing industry in Nigeria has de-industrialized because of the integration of the domestic economy to global capitalism. The textile industry used to be the third largest in Africa after Egypt and South Africa but this previous capacity has progressively declined over the years. The decline has been traced in part to the integration of the global economy, the policy of Structural Adjustment Program (SAP) and some domestic policy failures. The study used the dependency theory as the theoretical model and the secondary sources of data as the framework of analysis. The study found that the integration of the global economy and the SAP with its twin policies of trade deregulation and economic liberalization had led to the de-industrialization of the textile industry in Nigeria. The study revealed that the failure of some government policies has led to the progressive decline in the fortunes of the textile industry. The study also discovered that there is the urgent need for government to rethink globalization because of its dawn sizing effect on the domestic economy. Based on the findings, the study recommends that government should develop a thirty-year strategic road map for the Cotton, Textile and Garments (CTG) sub-sector as a response to global capitalism because it is strategic to national development. The study recommends that the aspect of the May 2017 Executive Order 003 dealing with the textile industry should now be forwarded to the National Assembly as an Executive Bill and seek to ensure that all uniformed agencies procure their garment materials and accessories locally as a way of boosting the capacity of the sector. The study recommends that the emerging New World Order with patriotism, protectionism and nationalism as key political and economic drivers should guide government policy actions rather than global expectations.